Systems pharmacology-based dissection of mechanisms of Tibetan medicinal compound Ruteng as an effective treatment for collagen-induced arthritis rats. (23rd May 2021) - Huang, Xian-Ju; Wang, Jing; Muhammad, Azhar; Tong, Hai-Ying; Wang, Da-Gui; Li, Jun; Ihsan, Awais; Yang, Guang-Zhong
Abstract: Ethnopharmacological relevance: Compound Ruteng (CRT) is a prescribed formulation based on the theory of Tibetan medicine for the treatment of yellow-water-disease. It is consisted with 7 medicinal material include Boswellia carterii Birdw (named "Ruxiang" in Chinese); Tinospora sinensis (Lour.) Merr. (named "Kuan-Jin-Teng" in Chinese), Cassia obtusifolia L (named "Jue-Ming-Zi" in Chinese); Abelmoschus manihot (L.) Medic (named "Huang-Kui-Zi" in Chinese); Terminalia chebula Retz. (named "He-Zi" in Chinese); Lamiophlomis rotata (Benth.) Kudo (named "Du-Yi-Wei" in Chinese) and Pyrethrum tatsienense (Bur. et Franch.) Ling (named "Da-Jian-Ju" in Chinese). They are widely distributed in Tibet area of China and have been used to treat rheumatism, jaundice, and skin diseases for centuries. Aim of the study: The present study was conducted to investigate the anti-arthritis effect of CRT and to disclose the systems pharmacology-based dissection of mechanisms. Materials and methods: The chemical constituents in CRT were identified using HPLC method, and CRT candidate targets against RA were screened by network pharmacology-based analysis and further experimentally validated based on collagen-induced arthritis (CIA) rat model. Furthermore, therapeutic mechanisms and pathways of CRT were investigated. Results: 391 potential targets (protein) were predicted against 92 active ingredients of 7 medicinal materials in CRT. Enrichment analysis and molecular docking studies also enforced the practiced results. X-ray based physiological imaging showed the attenuated effect of CRT on paw swelling, synovial joints and cartilage with improved inflammation in CIA rats. Moreover, the expression of biomarkers associated with RA such as MMP1, MMP3 and MMP13 and TNF-a, COX2 and iNOS are down-regulated in ankle joints, serum, or liver. Conclusion: In conclusion, CRT compound could attenuate RA symptoms and active ingredients of this compound could be considered for drug designing to treat RA. Graphical abstract: Image 1 Highlights: System pharmacology approach is applied to retrieve active ingredient and potential target in Compound Ruteng (CRT). CRT could attenuate paw swelling, synovial joints and cartilage with improved inflammation in collagen-induced arthritis (CIA) rats. CRT suppressed the production of inflammatory cytokines, oxidative stress indexes, MAPK pathway and regulate MMPs imbalance.